Analisis Upaya Pembaruan (Tajdid) Fikih dari Taklid - Usman, Mukran H.; Azwar, Azwar; Aswar, Aswar (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
This research aims to describe the various factors behind the phenomenon of taqlid in fiqh, analyze the factors causing the impasse in fiqh in Islamic countries, and present the efforts at tajdid fiqh that have been carried out in various spheres and fields of life. This research uses a descriptive-qualitative method with a normative, historical, and phenomenal approach. The research results show several things. First, the main cause of the decline of jurisprudence is the disease of Islamic faith that befalls the people. Second, there is a stalemate in jurisprudence so that the application of jurisprudence laws in various areas of life cannot be applied due to colonialism in many Islamic countries, a secular education system that eliminates Islamic religious education lessons in schools, errors in interpreting the meaning of worship, and a breakdown in communication between ulama in each Islamic country. Third, in the midst of the existence of Muslims who are declining due to the disease of taqlid, on the other hand, there are visible efforts to reform, namely in the form of the emergence of Islamic movements in various countries, the presence of various centers and research institutions of jurisprudence and law in various Islamic countries, the presence of various major projects in the field of jurisprudence in the form of the creation of the Encyclopedia of Islamic Jurisprudence, and the presence of the jurisprudence writing movement.penelitian), hasil kajian atau penelitian, dan simpulan.